Produksi dan Pemurnian Xilooligosakarida dari Xilan Tongkol Jagung menggunakan Xilanase Streptomyces P26B4 dan Khamir IP4 - Titi Candra Sunarti; Andika Susantri; Anja Meryandini (Institut Pertanian Bogor, 2021)
Xylooligosaccharides (XOS) are sugar oligomers from xylan that can be used as prebiotics to improve digestive tract health. Xylan can be extracted from corncobs which are a by-product of agriculture. The purpose of this study was to produce XOS through hydrolysis of corn cobs xylan using Streptomyces P26B4 xylanase. The products of hydrolysis also consisted of monomer xylose; for that xilooligosaccharides were purified using yeast IP4. The xylan hydrolysis products are quantitatively analyzed based on the value of reducing sugars and degree of polymerization (DP), strengthened qualitatively with TLC. Sugar component was analyzed after the addition of yeast by HPLC. P26B4 xylanase isolates had the highest activity on the 7th day incubation, pH 5,5 buffer citrate and temperature of 50°C. The lowest DP value of xylan hydrolysis was 2.49 at a concentration of 6%, and the 24th hour of incubation. TLC chromatograms showed that xylose and XOS products were produced. Purification of XOS at 6%, showed a decreasing in the area of xylose before and after receiving yeast respectively 1.87% and 1.41%.Therefore, yeast IP4 has the potential to consume xylose amnd purify the XOS. Keywords: corncobs xylan, IP4 yeast, purification, Streptomyces P26B4 xylanase, xylooligosaccharides